Modern strategies for the prevention and treatment of post-burn scars (a systematic review) - A. S. Umnikov; I. I. Glazko; E. I. Balakin; A. S. Samoilov; V. I. Pustovoit (Вестник трансплантологии и искусственных органов)
Despite advancements in modern reconstructive surgery, preventing the formation of thick scar tissue that impairs limb function or causes cosmetic defects remains a critical challenge. Equally important is the effective correction of existing scars to optimize both functional and aesthetic outcomes. Severe functional impairment of the upper limbs can result in disability. A combination of surgical and nonsurgical interventions is essential to enhance functionality while minimizing the risk of scar recurrence. Platelet-rich plasma injections, stem cell therapy, adipose tissue transplantation, and a combination of negative pressure wound therapy (NPWT) with traditional flap reconstruction and other transplantation methods are gaining popularity in modern reconstructive surgery. NPWT plays a crucial role in preparing the wound bed for subsequent tissue reconstruction and serves as an effective alternative to traditional dressings. The vacuum created over the wound after closure with a skin autograft helps prevent inflammation at the graft base, reduces excessive granulation tissue formation, and minimizes the risk of rough scar development in the long term. The mechanisms of formation of hypertrophic scar and keloids have not yet been completely understood. However, research indicates that bone marrow-derived cells, including fibrocytes and keratinocyte-like cells, contribute to the inflammatory cell infiltrate during wound healing, and can play a role in cutaneous fibrosis, especially in cases of impaired healing. Several pathophysiological and biochemical processes involved in the repair of extensive and deep wounds have been established. Additionally, the role of keratinocytes within hair follicle bulbs in promoting epithelialization of post-burn wound surfaces, particularly in areas with preserved skin appendages, has been recognized. Studies indicate that stromal-vascular fraction of adipose tissue plays a positive role in various stages of wound healing, including keloid and hypertrophic scar formation. Adipose-derived stem cells can be used in combination with hydrogel. The hydrogel base of dressings maintains a moist environment in both burn wounds and wound surfaces following tangential or radical excision of burn scab. This promotes faster wound healing, reduces the risk of scar hyperplasia, and enhances the sustained release and effectiveness of medications applied to the hydrogel base. Prompt surgical intervention, including early excision and grafting, along with modern treatment methods in the early postoperative period for deep burns, can significantly reduce the risk of hypertrophic and keloid scar formation.